Innovations barriers in the brazilian industry: a sectorial analysis - Maia, Mariana de Melo Alexandre (2016)
The objective of this article is to analyse the obstacles to innovate and their differences between the perceptions in different sectors of Brazilian industry. To achieve this objective, after to present descriptive data, we used multivariate statistical techniques: Cluster analysis of sectors with the same general behaviour and Multivariate Analysis Of VAriance (M)ANOVA to differentiate the variation of the factors in sectorial Cluster. The database used was the PINTEC 2009-2011 (IBGE, 2013). Identified the main obstacles, cost, lack of personnel, economic risks and financing. The results show the formation of six clusters grouping sectors with close characteristic obstacles, and analysis of factors by MANOVA indicate that less discriminated factors are economic risks, organizational rigidity and high costs of innovation.